The Calcium Carbonate Shell of Emiliania huxleyi Provides Limited Protection Against Viral Infection - Haunost, Mathias; Riebesell, Ulf; Bach, Lennart T. (Frontiers in Marine Science, 2020)
Coccolithophores are an important group of marine phytoplankton which cover themselves with the coccosphere – a shell composed of numerous calcium carbonate (CaCO3) platelets. Despite more than a century of coccolithophore research, it remains speculative why coccolithophores calcify. Resolving this question is essential to assess the competitive fitness of coccolithophores in the future ocean where changes in calcification are expected. Here, we used the Emiliania huxleyi – Emiliania huxleyi Virus 86 host-virus model system to test the hypothesis that the coccosphere serves as a physical barrier reducing viral infection. Therefore, we removed the coccosphere from living E. huxleyi cells and compared the infection progress relative to calcified cells in a series of 6 experiments under different growth conditions. We found that the coccosphere does not constitute an effective physical barrier against viral penetration, since non-growing calcified cells were susceptible to viral infection and lysis (growth stopped by light limitation). However, we also found that protection against the virus may depend on the daily growth cycle. E. huxleyi reached higher peak abundances when decalcified cells were allowed to rebuild their coccosphere before entering cell division phase and being exposed to the virus, thereby suggesting that rates of viral infection could be reduced by the coccosphere during the critical phase in the cell cycle. However, the benefit of this potential protection is arguably of limited ecological significance since the concentrations of both, calcified and decalcified E. huxleyi approached similar values until the end of the bloom. We conclude that the coccosphere provides at best a limited protection against infection with the EhV86.